Tiger, tyrant, bandit, businessman : echoes of counterrevolution from New China - DeMare, Brian James (Stanford University Press, 2022)
"The rural county of Poyang, lying in northern Jiangxi Province, goes largely unmentioned in the annals of modern Chinese history. While previously overlooked, Poyang provides the setting for this groundbreaking study of the dawn of the People's Republic of China in the countryside. Drawing on exceedingly rare resources from the county's Public Security Bureau, Tiger, Tyrant, Bandit, Businessman explores the early years of China's rural revolution through four true-crime tales of counterrevolution in Poyang. Using a unique casefile approach, Brian DeMare recounts stories of a Confucian scholar who found himself allied with bandits and secret society members, a farmer who murdered a cadre, an evil tyrant who exploited religious traditions to avoid prosecution, and a merchant accused of a crime he did not commit. Each case is a tremendous tale, complete with memorable characters, plot twists, and drama. And while all depict the enemies of New China, each also reveals details of village life during this most pivotal moment of recent Chinese history. Balancing storytelling with historical inquiry, while noting its limitations, this book is at once a grassroots view of rural China's legal system and its application to apparent counterrevolutionaries, and a lesson in archival research itself. Together, the narratives bring rural regime change to life, illustrating how the Chinese Communist Party cemented its authority through mass political campaigns, careful legal investigations, and sheer patience"--